Slip distribution of the 2005 Nias earthquake (Mw 8.6) inferred from geodetic and far-field tsunami data. Issue 2 (31st August 2020) - Fujii, Yushiro; Satake, Kenji; Watada, Shingo; Ho, Tung-Cheng
SUMMARY: We estimated the slip distribution on the fault of the 2005 Nias earthquake ( M w 8.6) by inversions of local GPS and coastal uplift/subsidence data and tsunami waveform data. The 2005 Nias earthquake occurred approximately three months after the 2004 Sumatra–Andaman earthquake ( M w 9.1) at the southern extension off Sumatra Island, Indonesia. The tsunami from the 2005 earthquake caused significantly less damage than the 2004 tsunami, yet was recorded at tide gauges and ocean bottom pressure gauges around the Indian Ocean, including the coasts of Africa and Antarctica. The elastic and gravitational coupling between the solid earth and the ocean causes not only a traveltime delay but also the change of waveforms of far-field tsunamis relative to the prediction based on the long-wave theory. We corrected the computed tsunami Green's functions for the elastic and gravitational coupling effect in the tsunami waveform inversion. We found a diffused slip (∼2 m over an area of 400 km × 100 km) at deeper parts (20–54 km) of the fault with a large localized slip (7 m over 100 km × 100 km) slightly south of the epicentre. The large slips at deeper parts of the fault were responsible for the small tsunami generation. Inversion using far-field tsunami data yielded a slip distribution similar to that obtained using local geodetic data alone and that from the joint inversion of local geodetic and far-field tsunami data, which is also similar to slip distributions from previous studies based on local geodetic data. This demonstrates that far-field tsunami waveforms, once corrected for propagation effects, can be used to estimate the slip distribution of large submarine earthquakes leading to results that are similar to those obtained using sparse local geodetic data.